A case-control investigation of the relation between hyperlipidaemia and calcific aortic valve stenosis. Issue 5 (1st November 1997) - Wilmshurst, P T; Stevenson, R N; Griffiths, H; Lord, J R
Abstract : Objective: To investigate the relation of hyperlipidaemia to calcific aortic valve stenosis. Design: A case-control study designed to detect a clinically relevant difference in the fasting plasma concentrations of total cholesterol between the groups at the 5% level with a power of 90%. Predefined subgroup analyses were based on presence of significant coronary disease and valve morphology (that is, bicuspid or tricuspid). Setting: A district general hospital. Subjects: 20 patients with severe calcific aortic stenosis and 20 controls. Results: Mean (SD) fasting plasma total cholesterol in patients with aortic stenosis was 0.79 (1.50) mmol/l greater than in the controls (p = 0.029). The magnitude of differences between patients with aortic stenosis and controls was similar whether the patients had coronary artery disease (0.78 (1.73) mmol/l) or not (0.80 (1.37) mmol/l). The presence of a stenosed tricuspid aortic valve was associated with a significant increase in plasma cholesterol (1.70 (0.87) mmol/l, p = 0.012). For bicuspid valves the degree of elevation of plasma cholesterol was less and not statistically significant. Conclusions: Calcific aortic stenosis is associated with hypercholesterolaemia, especially when the valve is tricuspid. Further studies are necessary to confirm that the relation is causal. This finding may have implications for measures to prevent the most common cause of cardiac valve replacement in the developed world.